Infarct-related artery and long-term mortality following recurrent ST-elevation myocardial infarction; insights from a Polish nationwide registry. (25th November 2020) - Wolny, R; Desperak, P; Kwiecinski, J; Gasior, M; Witkowski, A
Abstract: Background: Recurrent ST-elevation myocardial infarction (rSTEMI) occurs either as an acute thrombotic event in the same (target-vessel, TV-STEMI) or different vessel (non-target, nonTV-STEMI) compared with the first infarction. Little is known about the frequency of rSTEMI in the era of primary percutaneous coronary intervention (PCI) and about the impact of the infarct-related artery (IRA) on long-term prognosis. Purpose: We hypothesized that long-term mortality after rSTEMI varies according to IRA (either same or different compared with first STEMI). Methods: We retrospectively analysed data from the Polish Registry of Acute Coronary Syndromes (PL-ACS) and identified survivors of first STEMI treated with PCI who experienced rSTEMI and were discharged home. We divided rSTEMI into TV-STEMI and nonTV-STEMI group. We compared baseline clinical, angiographic and procedural characteristics and utilized propensity score matching to adjust for baseline differences. 1-, 3- and 5-year all-cause mortality was obtained from the Polish National Health Fund. Categorical variables were presented as counts and percentages and compared using Chi 2 test. Continuous variables were presented as medians and interquartile ranges and compared using Mann-Whitney test. The registry was approved by local Ethics Committee and meets the conditions of the Declaration of Helsinki Results: Between January 2003 and August 2019 a total of 3517 patients (mean age 62.9 years, 75% male) had rSTEMI, of whom 1941 (55%) had TV- and 1576 (45%) had nonTV-STEMI after 615 (77, 1683) days since first infarction (Figure 1). Patients with nonTV-STEMI had higher BMI (27.2 vs 26.8 kg/m 2, p=0.03), more hypertension (76.9 vs. 73.5%, p=0.02) and atrial fibrillation (4.7 vs. 3.3%, p=0.04), but had lower left ventricular ejection fraction (43 [35, 50] vs. 45 [38, 50], p<0.001) compared with TV-STEMI. On coronary angiography nonTV-STEMI had more frequently TIMI flow ≥1 (44.9 vs. 28.0%, p<0.001), multivessel disease (51.8 vs. 41.1%, p=0.003), culprit lesion located in circumflex artery (15.2 vs. 4.8, p<0.001) and more frequently underwent stenting (88.4 vs. 76.1%, p<0.001) compared with TV-STEMI. There was no difference in unadjusted 1-, 3- and 5-year mortality between nonTV-STEMI and TV-STEMI group (14.9 vs. 14.7%, p=0.9; 23.4 vs. 24.2%, p=0.64 and 29.6 vs. 32.9%, p=0.1 respectively). The propensity-score matching of 825 patients with TV- and 826 patients with nonTV STEMI suppressed all baseline differences, but adjusted mortality remained similar between study groups (Figure 1). Conclusion: While patients with recurrent nonTV-STEMI have different clinical and angiographic characteristics compared with TV-STEMI, the long-term mortality in these groups is similar. Funding Acknowledgement: Type of funding source: None